Respuesta :
Answer:
2c put me as brainlest
Step-by-step explanation:
Let's solve for c.
b=2c+6
Step 1: Flip the equation.
2c+6=b
Step 2: Add -6 to both sides.
2c+6+−6=b+−6
2c=b−6
Step 3: Divide both sides by 2.
2c
2
=
b−6
2
c=
1
2
b−3
Answer:
c=
1
2
b−3
now if ur just looking for the funtipn the asnwer would be 2c i think
Answer:
B. -6+8d-2c C. -2c+8d-6
Step-by-step explanation:
In order to determine which expressions are equivalent to you need to set the expression equal to the options available.